MODEL BERMAIN SULAP DALAM PEMBELAJARAN MENULIS BERITA KELAS VIII SMP - Wahyu Puji Hanggoro (Center of Language and Cultural Studies, 2015)
The objective of this paper is to describe how teaching to write news using creative and innovative techniques. The model is BERMAIN SULAP an acronym of Cover the News, Use recording tools, Recall evidences in the sites, Organize, and Report. The product being described in this paper is an instructional model explaining how writing news is developed for teaching for the grade VIII SMP students and steps to teach news using Bermain Sulat techniques. This model is designed based upon instructional objective in the School Based Curriculum 2006 (KTSP) incurring benefuts and weaknesses of the model.